«Charts Power» - International Ratings As An Economic Weapon And A Tool Of Soft Power. Part I - Ivanov, V G; Ivanova, M G (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2015)
In the given article, the authors propose and operationalize the notion of “charts power” (or “index power”, “ratings power”) as a significant component of soft power of national states and international institutions. The authors prove that numerous comparative ratings of different countries that have become extremely popular in recent decades could be used as an economic weapon and an effective tool of influence. The article analyses the mechanisms of ratings power and emergence of “rating thinking”. The authors conclude about the importance of actual and potential threats to national security of the Russian Federation from charts power of the foreign states.